Rapid manufacturing of bioceramic/polymer composite implants by selective laser sintering. (23rd June 2009) - Hao, L.; Savalani, M.M.; Harris, R.A.; Zhang, Y., K.E. Tanner
Selective Laser Sintering (SLS), an additive rapid manufacturing technique, is capable of producing the required product directly and automatically from a Three-Dimensional (3D) computer model representation. SLS has been selected to build implant and scaffold structures using composite materials consisting of a polymer and a bioactive ceramic. HydroxyApatite (HA), a bioceramic that encourages bone apposition, can be combined with High Density PolyEthylene (HDPE), a biocompatible polymer, to form a material with appropriate stiffness, toughness and bioactivity for use in the body. A miniature SLS system was built to minimise the usage of the expensive experimental material. It was used to determine the CO2 laser sintering operation window of the HA/HDPE composites and to investigate the effect of the process parameters on the surface morphology of the sintered HA/HDPE layer. The potential of SLS for the rapid manufacture of customised implants using HA/HDPE composite is demonstrated by the sintering of a five-layer HA-HDPE block.